Voltage-controlled floating resistor using DDCC - Kumngern, Montree; Torteanchai, Usa; Dejhan, Kobchai (My University, 2011)
This paper presents a new simple configuration to realize the voltage-controlled floating resistor, which is suitable for integrated circuit implementation. The proposed resistor is composed of three main components: MOS transistor operating in the non-saturation region, DDCC, and MOS voltage divider. The MOS transistor operating in the non-saturation region is used to configure a floating linear resistor. The DDCC and the MOS transistor voltage divider are used for canceling the nonlinear component term of MOS transistor in the non-saturation region to obtain a linear current/voltage relationship. The DDCC is employed to provide a simple summer of the circuit. This circuit offers an ease for realizing the voltage divider circuit and the temperature effect that includes in term of threshold voltage can be compensated. The proposed configuration employs only 16 MOS transistors. The performances of the proposed circuit are simulated with PSPICE to confirm the presented theory.
Keywords: CMOS; Differential difference current conveyor (DDCC); Floating resistor; Voltage-controlled resistor